E-health technologies and improving patient safety exploring organizational factors - Moumtzoglou, Anastasius, 1959-; Kastania, Anastasia, 1965- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book presents an overview of information and communication technologies and their impact on the field of both patient safety and e-health and highlights a better understanding of their interaction"--Provided by publisher.